Prostaglandin (PG)E(2) exhibits anti-fibrotic activity in vocal fold fibroblasts - Zhou, Hang (2011)
OBJECTIVES/HYPOTHESIS: Prostaglandin (PG)E(2) has been implicated in a variety of disease processes. It has been described as antifibrotic in the lower airway, yet scar-inducing in the skin. We seek to describe the effects of PGE(2) on vocal fold fibroblasts and its interactions with TGF-β1. In addition, we describe a novel organotypic model, a critical step in the development of therapeutic trials. STUDY DESIGN: In vitro, ex vivo LEVEL OF EVIDENCE: N/A METHODS: Collagen secretion by human vocal fold fibroblasts (HVFF) was assayed in response to TGF-β1, PGE(2), and specific EP receptor agonists. Basal HVFF migratory rate was also quantified in response to PGE(2). TGF-β1 induced COX-2 mRNA expression/PGE(2) secretion. Excised vocal folds were subjected to exogenous IL-1β; PGE(2) secretion into the supernatant was then assayed. RESULTS: TGF-β1-induced collagen secretion was blunted in a dose-dependent manner in response to PGE(2). This effect appears to be mediated primarily through the EP1 and EP2 receptors. TGF-β1 induced COX-2 mRNA expression and PGE(2) secretion. In our organ culture model, IL-1β stimulated PGE(2) secretion in a dose-dependent manner. CONCLUSIONS: PGE(2) is anti-fibrotic; this finding suggests that the upper airway response to this inflammatory mediator differs significantly from the lower airway. These data have important clinical implications for a variety of pathological processes. Furthermore, exogenous TGF-β1 elicits induction of COX-2, suggesting inherent complexity regarding these processes and PGE(2), signaling specifically. In addition, our organ culture model may prove useful as a means to quantify biological phenomena in the vocal folds.